A Useful Method for Preparing Mixed Brush Polymer Grafted Nanoparticles by Polymerizing Block Copolymers from Surfaces with Reversed Monomer Addition Sequence. Issue 19 (14th August 2017) - Zheng, Yang; Huang, Yucheng; Benicewicz, Brian C.
Abstract : This paper describes the utilization of the low blocking efficiency of reversed monomer addition order (i.e., the "wrong order") in combination with surface‐initiated reversible addition−fragmentation chain‐transfer polymerization to establish a facile procedure toward mixed polymer‐brush‐grafted nanoparticles SiO2 ‐g‐(PS, PS‐ b ‐PMAA). Additionally, the SiO2 ‐ b ‐(PS, PS‐ b ‐PMAA) nanoparticles are amphiphilic in nature and show unique and controllable self‐assembly behavior in water. Abstract : The preparation of well‐defined block copolymers using controlled radical polymerization depends on the proper order of monomer addition. The reversed order of monomer addition results in a mixture of block copolymer and homopolymer and thus has typically been avoided. In this paper, the low blocking efficiency of reversed monomer addition order is utilized in combination with surface initiated reversible addition−fragmentation chain‐transfer polymerization to establish a facile procedure toward mixed polymer brush grafted nanoparticles SiO2 ‐ g ‐(PS (polystyrene), PS‐ b ‐PMAA (polymethacrylic acid)). The SiO2 ‐ g ‐(PS, PS‐ b ‐PMAA) nanoparticles are analyzed by gel permeation chromatography deconvolution, and the fraction of each polymer component is calculated. Additionally, the SiO2 ‐ g ‐(PS, PS‐ b ‐PMAA) are amphiphilic in nature and show unique self‐assembly behavior in water.